Self-medication in academics of a public university in the south of Minas Gerais. - Cristina Martiniano MONTANARI; Walneia Aparecida de SOUZA; Daniela Oliveira VILELA; Fernando Sousa ARAÚJO; Márcia Helena Miranda Cardoso PODESTÁ; Eric Batista FERREIRA (Universidade de Brasília, 2015)
Introduction: Self-medication is a common practice anywhere in the world and the study of drug use is recognized as an important indicator in identifying the major pathologies in specific populations, estimating the prevalence and enabling better understanding on how populations use therapeutic resources. Objective: The objective of the study was to verify the prevalence of self-medication among students of a public university in southern Minas Gerais and verify if the healthcare academics behave differently from the ones of humanities area. To this end, we performed a descriptive cross-sectional study with a sample of 200 students, with 100 in the area of ​​Health Science (group 1) and 100 of the area of Humanities (group 2). Results: The prevalence of self-medication was 96.9 % among students in group 1 and 82.6 % in group 2 (p = 0.002). The most commonly used classes of drugs were analgesics/antipyretics. The main responsible for the indication of the drug in group 1 was the pharmacist; and in group 2 relatives and friends (p = 0.002) Conclusion: The self-medication proved to be a frequent practice among academics, demonstrating the need to devise strategies to sensitize the academic community regarding this practice.